Hubungan Status gizi dengan kejadian anemia pada ibu hamil di wilayah kerja UPT Puskesmas Sawah - Tria padna, Alkeke; Apriyanti, Fitri; Dhilon, Dhini Anggraini (Evidence Midwifery Journal, 2024)
Anemia is a condition in which the number of red blood cells or the amount of hemoglobin (oxygen transport protein) is below normal. Most pregnant women experience anemia which is not dangerous. In pregnant women, anemia can increase the risk of complications during pregnancy and childbirth. Antepartum and postpartum hemorrhage are more common in anemic women and are more often fatal, because anemic women cannot tolerate blood loss. The impact of anemia on pregnancy varies from very mild complaints to disruption of pregnancy continuity (abortion, immature or premature birth), disruption of the labor process (inertia, atonia, prolonged labor, atonic bleeding), disorders during the postpartum period (uterine sub-involution, endurance against infection and stress, low breast milk production), and disorders of the fetus (abortion, dysmaturity, microsomy, LBW, perinatal death). The aim of this research is to determine the correlation between nutritional status and the incidence of anemia in pregnant women in the UPT work area of ??the Sawah Community Health Center in 2022. This research design uses quantitative research methods with a case control approach. Case samples were taken using a retrospective approach. The samples were some pregnant women in the working area of ??the Sawah Community Health Center and the research population included all data on pregnant women in the working area of ??the Sawah Community Health Center in 2022 as many as 376 people. There were 57 normal pregnant women who were not anemic and 57 pregnant women with anemia. This research uses a check list sheet. Univariate data analysis with Chi-Squere test. The results of this study showed that there was a relationship between nutritional status and the incidence of anemia in pregnant women (P value 0.001) < (0.05). There is a relationship between nutritional status and the incidence of anemia in pregnant women in the UPT work area of ??the Sawah Community Health Center in 2022